Acoustics and Vibration of Mechanical Structures -- AVMS-2017 : proceedings of the 14th AVMS Conference, Timisoara, Romania, May 25-26, 2017 /: proceedings of the 14th AVMS Conference, Timisoara, Romania, May 25-26, 2017. (2018) - Unknown
No abstract available